ANALISIS PENGARUH STRUKTUR KOTA - SISTEM TRANSPORTASI - KONSUMSI BBM KOTA-KOTA DI JAWA - Handajani, Mudjiastuti (Jurnal Teknik Sipil dan Perencanaan, 2010)
Abstract:ÃÂ  TransportationÃÂ ÃÂ ÃÂ  sectorÃÂ  isÃÂ  sector withÃÂ  the mostÃÂ  customerÃÂ  fuel,ÃÂ  soÃÂ  fuelÃÂ  consumptionÃÂ  for transportationÃÂ  activityÃÂ  shouldÃÂ  appropriatelyÃÂ ÃÂ ÃÂ  getÃÂ  moreÃÂ  attention.ÃÂ  TheÃÂ  increasingÃÂ  activityÃÂ  of transportation syatem especiallyÃÂ  triggered byÃÂ  theÃÂ  increase of ownership and private vehicle usagegive negative impacts on towns. Ttransportation is sector taking the most fuel got from fossil source whichÃÂ  is gettingÃÂ  rare and unrenewable. Data collectedÃÂ  inÃÂ  thisÃÂ  researchÃÂ  is: a) data ofÃÂ  length ofÃÂ  the road,ÃÂ  theÃÂ  lengthÃÂ  ofÃÂ  theÃÂ  road,ÃÂ  onlyÃÂ  calculatedÃÂ  forÃÂ  asphaltedÃÂ  roadÃÂ  orÃÂ  reinforcedÃÂ  concrete,ÃÂ  b)ÃÂ  road network pattern,ÃÂ ÃÂ  in the field condition, road network patternÃÂ ÃÂ  does not always have the same form asÃÂ  roadÃÂ  networkÃÂ  patternÃÂ  inÃÂ  theÃÂ  theory,ÃÂ  ofÃÂ  (grid,ÃÂ  radial/concentric,ÃÂ  linear),ÃÂ  butÃÂ  thereÃÂ  areÃÂ  some modifications, c)ÃÂ  road condition, consisting of good,ÃÂ  relatively good, poor, and very poor condition category,ÃÂ  d)ÃÂ  passengerÃ¢â¬â¢sÃÂ  publicÃÂ  transportation,ÃÂ  consistingÃÂ  ofÃÂ  publicÃÂ  passengerÃÂ  transportationÃÂ  and publicÃÂ  bus,ÃÂ  e)goosÃÂ  transportation/truck,ÃÂ  f)ÃÂ  privateÃÂ  vehicleÃÂ  consistingÃÂ  ofÃÂ  passengerÃÂ  car,ÃÂ  busÃÂ  and motorcycle, g)ÃÂ  theÃÂ  length of designatedÃÂ  route of publicÃÂ  transportation. The highestÃÂ  influence ofÃÂ  the townÃÂ  structureÃÂ  onÃÂ  fuelÃÂ  consumptionÃÂ  isÃÂ  theÃÂ  numberÃÂ  ofÃÂ  people,ÃÂ  thatÃÂ  isÃÂ  0,986.TownÃÂ  transportation systemÃÂ  alsoÃÂ  hasÃÂ  theÃÂ  highÃÂ  influenceÃÂ  valuesÃÂ  onÃÂ  fuelÃÂ  consumption,ÃÂ  thatÃÂ  isÃÂ  0,907.ÃÂ  TownÃÂ  structure stronglyÃÂ  influencesÃÂ  fuelÃÂ  consumptionÃÂ  isÃÂ  strongerÃÂ  comparedÃÂ  toÃÂ  theÃÂ  transportationÃÂ  systemÃÂ  onÃÂ  fuel consumption. Key word:ÃÂ  influence, town structure, transportation system, fuel consumption. ÃÂ  Abstrak:ÃÂ  SektorÃÂ  transportasiÃÂ  merupakanÃÂ  konsumenÃÂ  yangÃÂ  palingÃÂ  banyakÃÂ  menggunakanÃÂ  BBM, sehingga konsumsi BBM untuk kegiatan transportasi selayaknya mendapat perhatian. Peningkatan kegiatan sistemÃÂ  transportasi khususnya yang dipicu oleh peningkatan pemilikan dan penggunaan kendaraan pribadi memberikan dampak negatifÃÂ  terhadap kota. Transportasi merupakan penyerap bahanÃÂ  bakarÃÂ  terbesarÃÂ  yangÃÂ  berasalÃÂ  dariÃÂ  sumberÃÂ  fosilÃÂ  yangÃÂ  semakinÃÂ  langkaÃÂ  danÃÂ  tidakÃÂ  dapat diperbaharui. Data yang dikumpulkan dalam penelitianÃÂ  ini adalahÃÂ  : a) data panjangÃÂ  jalan, panjang jalan, dihitung hanyaÃÂ  jalan yang aspal atau beton bertulang saja b) polaÃÂ  jaringanÃÂ  jalan, kondisi di lapangan polaÃÂ  jaringanÃÂ  jalanÃÂ  tidak selalu membentuk persis seperti polaÃÂ  jaringanÃÂ  jalan dalamÃÂ  teori (grid,ÃÂ  radial/konsentrik,ÃÂ  linear)ÃÂ  tetapiÃÂ  adaÃÂ  beberapaÃÂ  modifikasiÃÂ  c)ÃÂ  kondisiÃÂ  jalanÃÂ  yangÃÂ  terdiriÃÂ  dari kondisi baik, sedang,ÃÂ  rusak dan sangatÃÂ  rusak, d) kendaraan umum penumpang, yangÃÂ  terdiri dari MPUÃÂ  (mobilÃÂ  penumpangÃÂ  umum)ÃÂ  danÃÂ  busÃÂ  umumÃÂ  d)ÃÂ  angkutanÃÂ  barangÃÂ  (truk)ÃÂ  e)ÃÂ  kendaraanÃÂ  pribadi yangÃÂ  terdiriÃÂ  dariÃÂ  mobilÃÂ  penumpang,ÃÂ  bus,ÃÂ  danÃÂ  sepeda motorÃÂ  f)ÃÂ  panjangÃÂ  trayekÃÂ  angkutan ÃÂ umum. Pengaruh palingÃÂ  tinggi dari struktur kotaÃÂ  terhadapÃÂ  konsumsi BBM adalah Jumlah penduduk yaitu 0,986. SistemÃÂ  transportasiÃÂ ÃÂ ÃÂ  kotaÃÂ  juga mempunyaiÃÂ  nilaiÃÂ  pengaruhÃÂ  yangÃÂ  tinggiÃÂ  terhadapÃÂ  konsumsi BBMÃÂ  yaituÃÂ  0,907. StrukturÃÂ  kota mempengaruhi ÃÂ konsumsi BBMÃÂ  sangatÃÂ  kuatÃÂ  denganÃÂ  nilaiÃÂ  loading 0,976.ÃÂ  HubunganÃÂ  strukturÃÂ  kotaÃÂ  terhadapÃÂ  konsumsiÃÂ  BBMÃÂ  lebihÃÂ  kuatÃÂ  dibandingÃÂ  denganÃÂ  sistem transportasi terhadap konsumsi BBM. Kata kunci: pengaruh, struktur kota, sistem transportasi, konsumsi BBM.